Chemical profile and in-vitro pharmacological activities of yellow pigment extracted from Arthrobacter gandavensis. (December 2018) - Numan, Muhammad; Bashir, Samina; Mumtaz, Roqayya; Tayyab, Sibgha; Ullah, Ikram; Khan, Abdul Latif; Shinwari, Zabta Khan; Al-Harrasi, Ahmed
Graphical abstract: Abstract: Natural pigments have captivated pharmaceutical, food, textile and cosmetic markets because of its low toxicity as compared to synthetic pigments. Microorganisms, especially bacteria are the diverse source of natural pigments. The present study is performed with the aim to investigate different biological activities in pigment extracts from bacteria. A strain producing yellow pigment was identified as Arthrobacter gandavensis (Accession # MH187869) by 16S ribosomal RNA gene sequencing. Pigment was extracted and analyzed for various activities such as antibacterial, anticancer, antileishmanial, hemolytic, protein kinase inhibition and antioxidative activities. Total phenolic and flavonoid contents were also determined. An antibacterial study showed that the yellow pigment was found to be active against Klebsiella pneumoniae, Enterobacter sakazakii and Salmonella typhi with 10 ± 0.43 mm, 9 ± 0.77 mm and 80.98 mm zone of inhibition, respectively. Significantly high activity was noted against HepG2 cell lines (67%) at concentrations of 250 μg/mL and leishmania cell culture (82%) at concentrations of 1000 μg/mL were also noted. Similarly, results obtained from the other aforementioned activities were found to be dose-dependent, as the activity of the sample was found to be increased with a progressive increase in sample concentration. Some compounds (-Carotenold P468, capsorubin and 2-Butene-1-ol-3-methyl-acetate) were identified through HPLC and GCMS analysis. Similarly, results of the current study show that the yellow pigment is active in diverse biological activities. In conclusion, the yellow pigments isolated from Arthrobacter gandavensis covers a broad range pharmacological activities, which is ideal for industrial scale fermentation.